Open space design in historic urban environment - Balogh, Péter István (4D Journal of Landscape Architecture and Garden Art, 2006)
The goal of the study is to define the concept of urban open space design in historical environments, and to demonstrate, analyze and categorize the possible contemporary planning behaviours and design tendencies.